The Strategy of Preserving Reog Ponorogo Art in Local Cultural Heritage - Narwa Ramadhan, Anggara Giland (Journal Research of Social Science, Economics, and Management, 2026)
Abstract. This study aims to analyze the preservation strategies of Reog Ponorogo art in sustaining local culture, focusing on the role of the Reog Taruno Budoyo Art Community in Bungkal Village, Bungkal District, Ponorogo Regency. This research employs a qualitative descriptive method, with data collected through observation, in-depth interviews, and documentation. The results indicate that preservation strategies are implemented through cultural revitalization, educational integration, cultural digitalization, and community engagement. Cultural revitalization is carried out through routine training and performances supported by the local government. Educational integration is realized through school extracurricular activities, while cultural digitalization is conducted via social media for promotion and archiving. Community engagement is reflected in both moral and material support for art activities. However, preservation efforts still face challenges such as limited facilities, funding constraints, and declining youth interest. This study concludes that collaboration among government institutions, art communities, schools, and the broader community is key to sustaining Reog Ponorogo as a local cultural heritage identity.